Common practical questions – and answers – at the British Association for Psychopharmacology child and adolescent psychopharmacology course. (February 2023) - Cortese, Samuele; Besag, Frank MC; Clark, Bruce; Hollis, Chris; Kilgariff, Joseph; Moreno, Carmen; Nicholls, Dasha; Wilkinson, Paul; Woodbury-Smith, Marc; Sharma, Aditya
The British Association for Psychopharmacology course on child and adolescent psychopharmacology has been run for more than 20 years and is currently a very popular course, attracting around 140 delegates/year from across the United Kingdom and abroad. As Faculty of recent sessions of the course, we have selected the most common questions we have been asked in recent years and provided evidence-based and/or expert-informed answers. We have included 27 questions and answers related to attention-deficit/hyperactivity disorder, anxiety and depressive disorders, autism spectrum disorder, bipolar disorder, eating disorders, epilepsy (in differential diagnosis or comorbid with mental health conditions), obsessive-compulsive disorder, personality disorders, psychotic spectrum disorders, and tics/Tourette syndrome in children and young people. We hope that this article will be helpful for prescribers in their daily clinical practice and we look forward to further, high-level evidence informing the answers to these and other questions in child and adolescent psychopharmacology.